Analisa Komparasi dan Uji Akurasi Model Altman, Grover, Springate dan Zmijewski dalam Mendiagnosis Kebangkrutan Emiten Saham Jasa Transportasi di Bursa Efek Indonesia Pada Masa Pandemi - Yuniar Fitriyani (J-MAS (Jurnal Manajemen dan Sains), 2023)
The transmission of the COVID-19 virus which has become a pandemic in almost all countries in the world has had an impact on economic driving sectors, especially transportation due to various government policies related to limiting community mobilization so that the decline in this sector will have a chain effect related to everything. A continuous decline in the revenue of a transportation company while the operational expenses that must be borne by the company can threaten the sustainability of the business, which in the end the company will go bankrupt. This research wants to find out the differences in assessing the potential for bankruptcy in issuers in the transportation services sector whose shares are listed on the stock exchange in 2018-2021 using the Altman, Grover, Zmijewski and Springate models. The purposive sampling technique used has found 8 issuers as a sample with 32 financial reports during the study period. The results of the study found that 19 financial reports were predicted to be bankrupt, 6 financial reports were predicted to be prone to bankruptcy and 7 financial reports were categorized as healthy according to the Altman model. The Grover model predicts that 10 financial statements have the potential to go bankrupt and 22 are predicted to be healthy. The Springate model predicts that 27 financial statements have the potential to go bankrupt and only 5 are healthy. The Zmijewski model actually predicts only 3 financial reports are in a state of bankruptcy, 29 financial reports are potentially healthy. The four models have significant differences, where the most accurate model in diagnosing the bankruptcy of issuers of transportation services stocks is Grover because it has an accuracy rate of 78%, while the Altman and Springate models have the lowest accuracy rate of 44%.